Business cycles in small, open economies: Evidence from panel data between 1900 and 2013 - Wataru Miyamoto; Thuy Lan Nguyen (Bank of Canada, 2016)
Using a novel data set for 17 countries dating from 1900 to 2013, we characterize business cycles in both small developed and developing countries in a model with financial frictions and a common shock structure. We estimate the model jointly for these 17 countries using Bayesian methods. We find that financial frictions are an important feature for not only developing countries but also small developed countries. Furthermore, business cycles in both groups of countries are marked with trend productivity shocks. Common disturbances explain one-third of the fluctuations in small, open economies (both developed and developing), especially during important worldwide phenomena.
Keywords: F41; F44; E13; E32; 330; Business fluctuations and cycles; Economic models; International topics